P elements in the saltans group of Drosophila: a new evaluation of their distribution and number of genomic insertion sites - de Castro, J. P.; Carareto, CMA (Elsevier B.V., 2004)
Few are studies on P elements that have addressed the saltans group. These studies had shown that species from the cordata and elliptica subgroups were devoid of any discernible P homologous sequences, while species from the parasaltans, sturtevanti, and saltans subgroups all contain P element sequences. Our analyses showed the presence of one to 15 P element insertion sites in species of the saltans group, including Drosophila neocordata and Drosophila emarginata (cordata and elliptica subgroups, respectively). From these species, only those from the parasaltans, sturtevanti, and saltans subgroups harbor canonical P elements and, only those of the last two subgroups seem to harbor putative full-sized elements. Due to the low similarity of the sequences found in D. neocordata and D. emarginata to those earlier described, we suggest that these sequences might be rudimental P element derivatives that were present in the ancestral of the subgenus Sophophora. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: insertion sites; D. neocordata; D. emarginata; P element; saltans group; sequence divergence